68Ga-prostate-specific membrane antigen PETCT-based response to androgen deprivation therapy in patients with prostate cancer. Issue 12 (December 2019) - Gupta, Priyamvada; Murthy, Vedang; Agarwal, Archi; Maitre, Madan; Mhatre, Nihit; Rangarajan, Venkatesh
Abstract : Objective: To assess the response of castration-naïve prostate cancer to androgen deprivation therapy (ADT) in 68 Ga-PSMA PETCT, and test the hypothesis of differential response in primary, nodal and metastatic lesions. Materials/methods: Patients with adenocarcinoma prostate with baseline 68 Ga-prostate-specific membrane antigen (PSMA) PETCT scan, and response scan after 3–12 months of ADT from 2014 to 2017 were analyzed. Change in radiotracer uptake in the prostate, involved regional nodes and distant metastasis was semiquantitatively assessed in paired scans using maximum standardized uptake value (SUVmax). Response was categorized into complete or partial response (CR, PR) or stable disease or progressive disease (SD, PD), and correlated with known prognostic factors. Results: Total 86 scans of 43 patients (17 metastatic, M+) were analyzed. After median 6 months of ADT, 0% primary, 23.3% nodes and 17.6% metastases showed CR; 18.6% primary, 8.3% nodes and 35% metastases showed PD. Prostate response was not significantly associated with any prognostic factor. Nodal response was higher in M0 than in M+ disease (CR 37 vs 4%, P = 0.003). Oligometastases responded better than polymetastases (CR/PR 62.5 vs 11.1%, P = 0.05). Decline in SUVmax of primary tumor correlated with decline in serum prostate-specific antigen (PSA) (90% of partial responders showed >80% decline in serum PSA vs 50% with PD, P = 0.06). Conclusion: Primary prostatic tumor seems less likely to respond to ADT than nodal or metastatic lesions. Residual primary uptake may guide patient selection for local therapy in (oligo) metastatic prostate cancer.